Spider Silk and the Silk of Egg Sacs with its Astonishing Concealed Attributes: A Review - Tanmaya R. Sethy; Janak Ahi (Journal of Natural Fibers, 2022)
Spiders often generate several forms of silk fiber, each with distinctive qualities befitting them with certain activities and biological processes. The egg sacs of spiders are multilayered, complex structures that contain fibers from a variety of glands. The female lays her eggs in egg sacs that are safe from both living and nonliving elements. There are a few reviews of spider webs and silk, but none of her egg sacs. Our understanding of the relationship between protein structure, mechanical characteristics, antimicrobial activity, and ecological role of these exceptional biomaterials will expand and improve by examining egg sac silk. We address the current state of knowledge about spider egg sac silk and its processing method, as well as the use of egg sac silk-based materials in biomedicine and materials engineering. This review elucidates the structure, fiber composition, defense mechanism, mechanical strength, coloration, and antimicrobial activity of egg sac silk fibers. Spider egg sac silk-based materials have the potential to lead to advanced resistant and usable materials, making them one of the most exciting areas of research in material science. Future researchers will be able to take a more holistic approach as a result of it.